Summary of methamphetamine use among Aboriginal and Torres Strait Islander people - Australian Indigenous HealthInfoNet (2020)
The Summary of methamphetamine use among Aboriginal and Torres Strait Islander people is a plain language publication that provides summarised and updated information from the Review of methamphetamine use among Aboriginal and Torres Strait Islander people(2019). It provides key information about methamphetamine use among Aboriginal and Torres Strait Islander people in a style that is easy to engage with. It is particularly useful for health workers and those studying in the field as a quick source of general information about: the physical and mental impacts of methamphetamine historical and social factors of use how common methamphetamine use is responses to use prevention and education harm reduction strategies and treatments related government policies and strategies